The role of progressive farmers in East Kolaka as opinion leaders: Effective communication strategies for organic rice innovation diffusion - Arimbawa, Putu; Limi, Muhammad Aswar; Sarinah; Bahari, Doddy Ismunandar (AGROMIX, 2025)
Introduction: Organic farming has emerged as a sustainable and environmentally friendly approach to food production. However, the adoption of organic farming practices in Indonesia remains slow. Progressive farmers have the potential to act as opinion leaders, accelerating the diffusion of innovations in organic rice farming. This study investigates the role of progressive farmers as opinion leaders in facilitating innovation diffusion for the development of organic paddy fields. Methods: A qualitative research design was employed, utilizing a case study method. Data were collected through in-depth interviews, focus group discussions, non-participant observations, and document analysis involving 17 participants, including progressive farmers, conventional farmers, and agricultural extension agents engaged in organic rice farming development. Data were analyzed descriptively using the framework of social learning theory. Results: Findings indicate that opinion leaders play a pivotal role as initiators, pioneers, information disseminators, and role models in promoting organic rice farming innovations. Their actions and statements regarding innovations strongly influence farmers' decision-making processes. Conclusion: The study concludes that progressive farmers, as opinion leaders, effectively act as change agents and mentors by introducing and fostering the adoption of organic farming practices. The shared socio-cultural background between opinion leaders and their communities facilitates intensive interpersonal communication, ensuring that messages are relevant, credible, memorable, and trustworthy, thereby accelerating innovation diffusion. Nevertheless, the study also highlights certain limitations faced by progressive farmers. Strengthening their communication skills and fostering collaborations with agricultural institutions, such as extension agents and organic farming communities, are essential to further expedite the diffusion of organic farming innovations.